Goethite (α-FeOOH) nanopowders synthesized via a surfactant-assisted hydrothermal method: morphology, magnetic properties and conversion to rice-like α-Fe2O3 after annealing. Issue 34 (15th April 2015) - Li, Dongyun; Hu, Xuzhao; Sun, Yukun; Su, Shubing; Xia, Ailin; Ge, Hongliang
<x xml:space="preserve">Abstract</x> Acicular goethite (α-FeOOH) nanopowders were synthesized at a high temperature via a CTAB-assisted hydrothermal method.